Management of Solid Medical Waste on One of the Covid19 Referral Hospitals in Surabaya, East Java - Rani Ayu Wardani; R. Azizah (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: e Covid19 virus has an outer lipid sheath that is not tolerant towards disinfectants, but this virus can quickly infect humans with a fairly high mortality rate. The increasing Covid19 patients directly proportional the amount of solid medical waste production in hospitals. This study aims to identify the health protocol in solid medical waste management in one of the Covid19 patient referral hospitals in Surabaya, East Java. Method: We used descriptive observational research with secondary data for the data compiling method. The obtained data were then compared with the 2020 Guidebook on Waste Management in Referral Hospitals, Emergency Hospitals, and Public Health Centers that Handles Covid19 Patients, issued by the Ministry of Health of the Republic of Indonesia. Result and Discussion: Research results showed that the management of all solid medical waste yielded from the Covid19 Special Isolation Room is directly infectious, went through the incineration process using an incinerator with the primary burner set at 800o C and the secondary burner set at minus 1.000o C. The usage of Personal Protective Equipment (PPE) by medical waste trolley carriers was inappropriate. The officers only used surgical masks, head caps, gloves, shirt, and work shoes, without using any apron. Conclusion: Health protocol for medical waste management in one of the Covid19 patient referral hospitals in Surabaya, East Java has been implemented, but the usage of PPE by medical waste trolley carriers was still inappropriate.